Morphological Variations of Distal End of Femur: A Cross-sectional Study - Jatin B Goda; Shailesh M Patel; Ajay M Parmar (International Journal of Anatomy Radiology and Surgery, 2022)
Introduction: Apart from intercondylar notch and trochlear groove, the intercondylar line also contributes to knee joint instability. Knowledge of morphological variations of these anatomical landmarks can help in diagnosis as well as planning the treatment. As of now, very limited data is available on morphological variations of trochlear groove and intercondylar line.